A Dilemma for 'Selection‐for‐Action'. (30th April 2018) - Buehler, Denis
Abstract: One of the most influential recent accounts of attention is Wayne Wu's. According to Wu, attention is selection‐for‐action. I argue that this proposal faces a dilemma: either it denies clear cases of attention capture, or it acknowledges these cases but classifies many inattentive episodes as attentive.